The TbD1 Locus Mediates a Hypoxia-Induced Copper Response in Mycobacterium bovis - Ma, Ruoyao; Farrell, Damien; Gonzalez, Gabriel; Browne, John A.; Nakajima, Chie; Suzuki, Yasuhiko; Gordon, Stephen V. (Frontiers in Microbiology, 2022)
The Mycobacterium tuberculosis complex (MTBC) contains the causative agents of tuberculosis (TB) in mammals. The archetypal members of the MTBC, Mycobacterium tuberculosis and Mycobacterium bovis, cause human tuberculosis and bovine tuberculosis, respectively. Although M. tuberculosis and M. bovis share over 99.9% genome identity, they show distinct host adaptation for humans and animals; hence, while the molecular basis of host adaptation is encoded in their genomes, the mechanistic basis of host tropism is still unclear. Exploration of the in vitro phenotypic consequences of known genetic difference between M. bovis and M. tuberculosis offers one route to explore genotype-phenotype links that may play a role in host adaptation. The TbD1 (‘Mycobacterium tuberculosis deletion 1 region’) locus encompasses the mmpS6 and mmpL6 genes. TbD1 is absent in M. tuberculosis ‘modern’ lineages (Lineages 2, 3, 4) but present in ‘ancestral’ M. tuberculosis (Lineage 1 and 7), M. africanum lineages (Lineage 5 and 6), newly identified M. tuberculosis lineages (Lineage 8 and 9), and animal adapted strains, such as M. bovis. The function of TbD1 has previously been investigated in M. tuberculosis, where conflicting data has emerged on the role of TbD1 in sensitivity to oxidative stress, while the underlying mechanistic basis of such a phenotype is unclear. In this study, we aimed to shed further light on the role of the TbD1 locus by exploring its function in M. bovis. Towards this, we constructed an M. bovis TbD1 knockout (ΔTbD1) strain and conducted comparative transcriptomics to define global gene expression profiles of M. bovis wild type (WT) and the ΔTbD1 strains under in vitro culture conditions (rolling and standing cultures). This analysis revealed differential induction of a hypoxia-driven copper response in WT and ΔTbD1 strains. In vitro phenotypic assays demonstrated that the deletion of TbD1 sensitized M. bovis to H2O2 and hypoxia-specific copper toxicity. Our study provides new information on the function of the TbD1 locus in M. bovis and its role in stress responses in the MTBC.